Diagnostic validity of the tests for assessing and monitoring football-playing abilities in boys - Molnar, S.; Doder, D.; Popovic, R.; Doder, R.; Smajic, M. (Homosporticus, 2010)
The system of 22 variables in total (12 morphological and 10 specific morphological ones) was applied to the sample that included 105 boys, aged 10, with the aim of determining diagnostic (factor) validity of the battery of tests for assessing and monitoring football-playing abilities in boys. Applying the factor analysis (direct oblimin, Kaiser l³1.00), in morphological and specific motor space two latent variables for each of them were isolated. The first morphological latent variable is defined using the variables for the assessment of body voluminosity and subcutaneous adipose tissue, while the other is defined by variables for the assessment of skeleton longitudinality and transversality. The first latent variable in specific motor space can be interpreted as a variable for assessing precision in hitting the target and a ball handling, while the other can be interpreted as a variable for the assessment of the speed of guiding the ball, the ball kick strength and the speed of curvilinear motion/running. Diagnostic validity of the battery of the tests for assessing and monitoring morphological characteristics and specific motor football-playing abilities in boys was determined applying the factor procedure by means of parallel projection matrix (matrix A), which is consisted of 5 morphological variables (body mass, body height, shinbone circumference, thigh skinfold, calf skinfold) and 5 specific motor variables (propelling the ball towards a goal through dribbling (running with the ball close to one`s feet) - with a foot, guiding the ball around the semicircle, guiding the ball in random directions, heading a ball over a long distance, striking a rolling ball (without settling it first) against the wall - with a foot).